Eliciting Life Priorities of Older Adults Living in Permanent Supportive Housing - Padgett, Deborah K (Gerontologist, 2020)
BACKGROUND AND OBJECTIVES: Adults who have experienced chronic homelessness are considered to be “old” by age 50 due to accelerated aging. While permanent supportive housing (PSH) has been found effective for these individuals, there is limited focus on the needs of adults “aging in place” in PSH. This study examined (1) how older adults in PSH identify and rank their life priorities, (2) how they describe these priorities in their own words, and (3) how life course adversity deepens an understanding of these priorities. RESEARCH DESIGN AND METHODS: A convergent parallel mixed methods design was used in which qualitative case study analyses informed by a life course perspective provided a deeper understanding of how 14 older residents of PSH viewed their life priorities using quantitative card-sort rankings of 12 life domains. RESULTS: Housing, family, mental health, physical health, and partner were the most frequently endorsed life priorities. Four themes emerged from the cross-case analyses: “aging in, aging out,” “carefully restoring relationships,” “life goes on,” and “housing is fundamental.” Convergent findings indicated that life adversity—social losses and interrupted lives—influenced both the high- and low-ranked card-sort priorities. DISCUSSION AND IMPLICATIONS: This study demonstrated that participants were aware of their advancing years yet they sought to overcome adversity and losses through maintaining mental health and sobriety, improving physical health, and cautiously rebuilding relationships. As the numbers of older homeless rise, the inclusion of age-related services will be an important component of PSH services for residents as they age.